Host-dependent editing of SARS-CoV-2 in COVID-19 patients. Issue 1 (1st January 2021) - Gregori, Josep; Cortese, Maria Francesca; Piñana, Maria; Campos, Carolina; Garcia-Cehic, Damir; Andrés, Cristina; Abril, Josep Francesc; Codina, Maria Gema; Rando, Ariadna; Esperalba, Juliana; Sulleiro, Elena; Joseph, Joan; et al.
ABSTRACT: A common trait among RNA viruses is their high capability to acquire genetic variability due to viral and host mechanisms. Next-generation sequencing (NGS) analysis enables the deep study of the viral quasispecies in samples from infected individuals. In this study, the viral quasispecies complexity and single nucleotide polymorphisms of the SARS-CoV-2 spike gene of coronavirus disease 2019 (COVID-19) patients with mild or severe disease were investigated using next-generation sequencing (Illumina platform). SARS-CoV-2 spike variability was higher in patients with long-lasting infection. Most substitutions found were present at frequencies lower than 1%, and had an A → G or T → C pattern, consistent with variants caused by adenosine deaminase acting on RNA-1 (ADAR1). ADAR1 affected a small fraction of replicating genomes, but produced multiple, mainly non-synonymous mutations. ADAR1 editing during replication rather than the RNA-dependent RNA polymerase (nsp12) was the predominant mechanism generating SARS-CoV-2 genetic variability. However, the mutations produced are not fixed in the infected human population, suggesting that ADAR1 may have an antiviral role, whereas nsp12-induced mutations occurring in patients with high viremia and persistent infection are the main source of new SARS-CoV-2 variants.